Low-complexity ESPRIT-based DOA estimation for MIMO radar with L-shaped array. Issue 1 (2nd January 2018) - Liang, H.; Cui, C.
ABSTRACT: Aiming at the problem of two-dimensional (2D) angles estimation for monostatic multiple-input–multiple-output radar with L-shaped array, a novel reduced-dimensional (RD) direction of arrival estimation (DOA) method based on estimation of signal parameters by rotational invariance techniques (ESPRIT) algorithm is proposed. First, through the RD matrix design and RD transformation, the higher dimensional received data can be transformed into a lower dimensional signal space. Then the signal space can be achieved via the eigen-value decomposition. Last, conjoint with the ESPRIT algorithm, 2D spatial angle parameters with automatic pairing can be jointly estimated. The proposed method can remove data redundancy of high dimensional received data at the greatest degree and enhance sensors efficiency without costing the aperture of array, with a result of better performance than 2D-ESPRIT algorithm. Moreover, compared with the multiple signal classification (MUSIC)-like algorithms, the proposed method has the better overall performance and is more available for a lower computation complexity and higher instantaneity of application. Simulation results verify that the correctness of theoretical analysis and the effectiveness of proposed algorithm.